KEMAMPUAN MEMAKNAI SIMBOL UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI - Sila, Gita Eka; hasim; Sabarudin, Didin (UKRI, 2025)
Communication reaches the broadest aspect of meaning. Its depth can reveal hidden and unexplained meanings. A complete understanding of symbols can explain something. The understanding obtained can point to objects or similar concepts that are easy to refer to. Communication obstacles occur when the concept referred to is given the wrong meaning. So that it becomes an obstacle in improving communication skills. Skills that are very much needed to help improve the capacity of each person. In this regard, this study aims to determine the ability to interpret symbols scattered in the social environment to improve communication skills. The method used is qualitative with a descriptive research type. The results of the study indicate that emotional intelligence is the main prerequisite in improving the ability to interpret symbols that are related to improving communication skills.